Persepsi Mahasiswa Terhadap Penggunaan ChatGPT di Era Pendidikan 4.0 - Juniarty Salmi; Angela Atik Setiyanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze student perceptions of the use of ChatGPT in the era of education 4.0. In an era of education characterized by technological development, ChatGPT as an artificial intelligence-based chatbot offers exciting potential. The research method used is qualitative with the Technology Acceptance Model (TAM) approach, and data collection is done through Google Form. The results of the analysis show that students have a positive perception of the use of ChatGPT in self-development, improving quality, creativity, time efficiency, and learning productivity. Students also feel happy and satisfied and have high motivation to use ChatGPT. However, there are several indicators that need to be considered in the development and implementation of ChatGPT, such as access difficulties and challenges to student creativity in writing. This research provides valuable insights for educational institutions and technology developers to optimize the use of artificial intelligence technology in students' learning experience in the education 4.0 era.